Duplication of C7orf58, WNT16 and FAM3C in an obese female with a t(7;22)(q32.1;q11.2) chromosomal translocation and clinical features resembling Coffin-Siris Syndrome. - Jun Zhu; Jun Qiu; Gregg Magrane; Malak Abedalthagafi; Andrea Zanko; Mahin Golabi; Farid F Chehab (PLoS ONE, 2012)
We characterized the t(7;22)(q32;q11.2) chromosomal translocation in an obese female with coarse features, short stature, developmental delay and a hypoplastic fifth digit. While these clinical features suggest Coffin-Siris Syndrome (CSS), we excluded a CSS diagnosis by exome sequencing based on the absence of deleterious mutations in six chromatin-remodeling genes recently shown to cause CSS. Thus, molecular characterization of her translocation could delineate genes that underlie other syndromes resembling CSS. Comparative genomic hybridization microarrays revealed on chromosome 7 the duplication of a 434,682 bp region that included the tail end of an uncharacterized gene termed C7orf58 (also called CPED1) and spanned the entire WNT16 and FAM3C genes. Because the translocation breakpoint on chromosome 22 did not disrupt any apparent gene, her disorder was deemed to result from the rearrangement on chromosome 7. Mapping of yeast and bacterial artificial chromosome clones by fluorescent in situ hybridization on chromosome spreads from this patient showed that the duplicated region and all three genes within it were located on both derivative chromosomes 7 and 22. Furthermore, DNA sequencing of exons and splice junctional regions from C7orf58, WNT16 and FAM3C revealed the presence of potential splice site and promoter mutations, thereby augmenting the detrimental effect of the duplicated genes. Hence, dysregulation and/or disruptions of C7orf58, WNT16 and FAM3C underlie the phenotype of this patient, serve as candidate genes for other individuals with similar clinical features and could provide insights into the physiological role of the novel gene C7orf58.